1985
DOI: 10.1523/jneurosci.05-12-03350.1985
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic connections of macaque striate cortex: axonal projections of cells outside lamina 4C

Abstract: We have exploited a technique for making small injections of horseradish peroxidase into single cortical laminae in order to study axonal projections in macaque striate cortex. In the preceding paper (Fitzpatrick, D., J. S. Lund, and G. G. Blasdel (1985) J. Neurosci. 5: 3329-3349) we examined the projections of cells in lamina 4C--cells that receive most of their input from the lateral geniculate nucleus. The present paper deals with the projections of neurons that lie outside of lamina 4C. Among our findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
111
2
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(125 citation statements)
references
References 11 publications
11
111
2
1
Order By: Relevance
“…In the latter case the possibility of uptake of biocytin by passing fibers remains open. Against this possibility is the fact that similar patterns of labeling are obtained irrespective of the amount of tissue damaged (8,16,31, and the present results). The first hypothesis, i.e., the same cells projecting both intrinsically and extrinsically, is supported by the results obtained after isolated injections into layers II and III or IVb (31) which show retrogradely labeled pyramidal cells and axon terminals forming patches in layers II and III.…”
Section: Cell Morphology and Laminar Distributionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the latter case the possibility of uptake of biocytin by passing fibers remains open. Against this possibility is the fact that similar patterns of labeling are obtained irrespective of the amount of tissue damaged (8,16,31, and the present results). The first hypothesis, i.e., the same cells projecting both intrinsically and extrinsically, is supported by the results obtained after isolated injections into layers II and III or IVb (31) which show retrogradely labeled pyramidal cells and axon terminals forming patches in layers II and III.…”
Section: Cell Morphology and Laminar Distributionsupporting
confidence: 83%
“…The present paper described retrogradely (31), these projections were asymmetrical in relation to the injection site, with strong labeling on one side as compared to the other. In cases of iontophoretic injections located in layers II and III the infragranular labeled cells were found in layer V, similar to the results reported by Livingstone and Hubel (14).…”
Section: Cell Morphology and Laminar Distributionsupporting
confidence: 45%
“…The laminar numbering system used in this and the following paper (Blasdel et al, 1985) is shown in Figure 1. Since certain laminar borders do not appear sharp in Nissl-stained sections, we have used the distribution of cytochrome oxidase activity, as well as cytoarchitecture, to define laminar borders (see Blasdel and Fitzpatrick, 1984, for further discussion).…”
Section: Resultsmentioning
confidence: 99%
“…In the following paper (Blasdel et al, 1985) we examine the interconnections of the remaining layers which constitute the source of projections to the thalamus, brainstem and to extrastriate cortex. Some of these results have been reported briefly (Blasdel et al, 1983;).…”
mentioning
confidence: 99%
“…Top-down inter-areal connections terminate in the supra-(layer 2/3) and infra-granular layers (layer 5/6). Using techniques of microinjections of D-3H-Asp and injections of horseradish peroxidase, very detailed intra-areal connections, including intra-laminar and lateral excitatory projections have been experimentally investigated Blasdel et al 1985 andKisvarday et al 1989).…”
Section: Introductionmentioning
confidence: 99%